2020
DOI: 10.1021/acs.jcim.0c00020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of X-ray Diffraction Patterns Based on Very Limited Data by Interpretable Convolutional Neural Networks

Abstract: Large volumes of data from material characterizations call for rapid and automatic data analysis to accelerate materials discovery. Herein, we report a convolutional neural network (CNN) that was trained based on theoretic data and very limited experimental data for fast identification of experimental X-ray diffraction (XRD) spectra of metal-organic frameworks (MOFs). To augment the data for training the model, noise was extracted from experimental spectra and shuffled, then merged with the main peaks that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 32 publications
(77 reference statements)
0
89
0
Order By: Relevance
“…Wang et al predicted the patterns for MOFs in the Cambridge Structure Database (CSD) and then augmented their data set by creating new patterns by merging the main peaks of the predicted patterns with (shuffled) noise from pattern they measured in their own lab. 135 …”
Section: Selecting the Data: Dealing With Little Imbalanced And Nonmentioning
confidence: 99%
“…Wang et al predicted the patterns for MOFs in the Cambridge Structure Database (CSD) and then augmented their data set by creating new patterns by merging the main peaks of the predicted patterns with (shuffled) noise from pattern they measured in their own lab. 135 …”
Section: Selecting the Data: Dealing With Little Imbalanced And Nonmentioning
confidence: 99%
“…As a final step, background and noise are added. Previous works extracted these components from measured signals (Wang et al, 2020) but we model the background using a highorder polynomial function (Chebyshev) and uncertainties of the measurement are represented by Gaussian noise, the same as in the work of Lee et al (2020). The inclusion of Gaussian noise in the simulated scans is necessary so that the network is able to distinguish between diffraction peaks and noise when applied to measured data.…”
Section: Addition Of Further Effectsmentioning
confidence: 99%
“…In application, highly specialized machine-learning algorithms, such as the non-negative matrix factorization (NMF) (Long et al, 2009) approach, as well as neural-network structures (Park et al, 2017) have already demonstrated good performance for the automatic analysis of XRD data. While the NMF approach learns to describe the diffraction pattern as a linear combination of phases with different fractions, neural networks interpret the diffraction scans as one-dimensional images and detect phases based on intensities under certain 2 angles (Oviedo et al, 2019;Wang et al, 2020). Previous works show that machine-and deep-learning models can be applied for space-group, extinction-group and crystal-system prediction (Oviedo et al, 2019;Park et al, 2017), and the assignment of diffraction patterns to their respective phases (Long et al, 2009;Wang et al, 2020;Stanev et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al 21 refined atomic pair distribution functions in a convolutional neural network (CNN) to classify SGs. For similar purposes, Park et al 22 , Vecsei et al 23 , Wang et al 24 , Oviedo et al 25 , and Aguiar et al 26 used powder X-ray diffraction (XRD) 1D curves, for which information such as peak positions, intensities, and fullwidths at half-maximum are mainly treated as the key input descriptors. In addition, Ziletti et al 27 (in a parent work of this study), Aguiar et al 28 , Kaufmann et al 29 , and Ziatdinov et al 30 developed DL models by extracting features from electron-beam based 2D DPs.…”
Section: Introductionmentioning
confidence: 99%